Repensar las artes : culturas, educación y cruce de itinerarios - Aguirre Lora, Georgina María Esther (IISUE Educación., 2011)
The work is an interesting and original approach which spans various times and places of the different facets of art education and artistic training in an effort to rethink art education in Mexico. A useful book not only to art and art history specialists but also to those interested in education.